The Impact of Environmental Policies on Corporate Strategies: A Systematic Review - Wahyuni, Wahyuni; Hazizah, Mawaddah Tuhfah; Ramadhani, Alya; Ahmad, Azis (Advances in Management & Financial Reporting, 2024)
Purpose: This systematic review investigates the complex relationship between environmental policies and corporate strategies, aiming to understand their mechanisms and impacts. The goal is to comprehensively analyze existing literature to determine how environmental policies shape firms' strategic behaviors and organizational outcomes. Research Design and Methodology: Employing a systematic approach, this study synthesizes diverse sources and disciplines to identify key drivers and barriers influencing firms' responses to environmental policies. Quantitative and qualitative methodologies are integrated to explore the dynamic relationship between regulatory compliance and corporate strategies. Findings and Discussion: The findings reveal that regulatory compliance drives innovation in firms, advancing sustainability practices and competitive advantage. Additionally, integrating environmental considerations into corporate governance enhances resilience and promotes a culture of sustainability. The discussion highlights the positive impact of regulatory-induced innovation on firms' strategic behaviors while acknowledging the challenges of regulatory complexities and financial constraints. Implications: The implications underscore the importance of proactive environmental management in navigating regulatory complexities and positioning firms for long-term success. This study contributes to advancing theoretical understanding and guiding managerial practice in fostering sustainable business practices and environmental stewardship within the corporate sector.